Microbial respiration in relation to temperature and moisture in fynbos soils of Swartboskloof, Jonkershoek - De Koker, Theodorus Hermanus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1994.